How many consumers are rational? - Stefan Hoderlein (Centre for Microdata Methods and Practice (cemmap), 2009)
Rationality places strong restrictions on individual consumer behavior. This paper is concerned with assessing the validity of the integrability constraints imposed by standard utility maximization, arising in classical consumer demand analysis. More specifically, we characterize the testable implications of negative semidefiniteness and symmetry of the Slutsky matrix across a heterogeneous population without assuming anything on the functional form of individual preferences. In the same spirit, homogeneity of degree zero is being considered. Our approach employs nonseparable models and is centered around a conditional independence assumption, which is sufficiently general to allow for endogenous regressors. It is the only substantial assumption a researcher has to specify in this model, and has to be evaluated with particular care. Finally, we apply all concepts to British household data: We show that rationality is an acceptable description for large parts of the population, regardless of whether we test on single or composite households.
Keywords: C12; C14; D12; D01; 330; Nonparametric; Integrability; Testing Rationality; Nonseparable Models; Demand; Nonparametric IV; Nichtparametrisches Verfahren; Statistischer Test; Konsumentenverhalten; Mikroökonometrie